Association of serum protein electrophoresis with clinicopathological characteristics and its prognostic relevance in chronic lymphocytic leukaemia patients - Hameed, Aisha; Nadia Sajid; Rabia Basri Javaid; Nadir Ali (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the association of serum protein electrophoresis abnormalities with clinicopathological characteristics, and its impact on overall survival in chronic lymphocytic leukaemia patients. Methods: The prospective study was conducted at Haematology and Immunology departments of the University of Health Sciences, Lahore, Pakistan, from 2019 to 2022, and comprised newly diagnosed chronic lymphocytic leukaemia patients. Lactate dehydrogenase and beta-2 microglobulin levels were measured by spectrophotometric principle, whereas serum protein electrophoresis was determined through commercially available capillary electrophoresis systems. Patients were followed up for 2 years post-diagnosis. Data was analysed using SPSS 21. Results: Of the 50 patientss, 40(80%) were males and 10(20%) were females. The overall mean age was 60±11 years. Serum protein electrophoresis was available for 40(80%) patients, and, among them, 12(30%) patients had abnormal levels, while 29(72.5%) required treatment. Overall response rate was 25(86.2%), and median two-year overall survival was 16.5 months (95% confidence interval: 10-20 months). Abnormal serum protein electrophoresis was significantly associated with Binet stage C, lower mean haemoglobin levels and higher median levels of lactate dehydrogenase and beta-2 microglobulin (p<0.05)). Regarding overall survival, the survival curves of chronic lymphocytic leukaemia patients with normal and abnormal serum protein electrophoresis status differed significantly (p=0.04). Conclusion: Abnormal serum protein electrophoresis could be considered a surrogate marker for advanced chronic lymphocytic leukaemia disease. Key Words: CLL, Serum protein electrophoresis, Overall survival, Pakistan.